PEMBUATAN HANDYCRAFT DAN PENGEMASAN PRODUK KARANG TARUNA KELURAHAN BALEKAMBANG JAKARTA TIMUR - Kanaria Herwati; Siska Maya; Siti Juriah (SYUKUR (Jurnal Inovasi Sosial dan Pengabdian Masyarakat), 2019)
The community service activity aims to provide skills training in making and packaging interesting handicrafts, training in calculating the selling price and increasing the creativity and innovation of the Karang Taruna group in the Balekambang Village, Kramat Jati, East Jakarta, especially youth clubs RW.03 and 04. The resulting product is a bouquet of flowers using flannel fabric.